2021
DOI: 10.1073/pnas.2020834118
|View full text |Cite
|
Sign up to set email alerts
|

The effects of school closures on SARS-CoV-2 among parents and teachers

Abstract: To reduce the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), most countries closed schools, despite uncertainty if school closures are an effective containment measure. At the onset of the pandemic, Swedish upper-secondary schools moved to online instruction, while lower-secondary schools remained open. This allows for a comparison of parents and teachers differently exposed to open and closed schools, but otherwise facing similar conditions. Leveraging rich Swedish register data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
119
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 29 publications
9
119
3
2
Order By: Relevance
“…If susceptibility increases with age, as some evidence suggests [21,39,64], we estimated that high school teachers may experience as much as 5-10 times greater risk of symptomatic infection than elementary school teachers, depending on the level of community transmission. These findings agree with empirical data from Sweden, which found that risk to teachers increased with student age [59].…”
Section: Discussionsupporting
confidence: 91%
“…If susceptibility increases with age, as some evidence suggests [21,39,64], we estimated that high school teachers may experience as much as 5-10 times greater risk of symptomatic infection than elementary school teachers, depending on the level of community transmission. These findings agree with empirical data from Sweden, which found that risk to teachers increased with student age [59].…”
Section: Discussionsupporting
confidence: 91%
“…This means that one of the main reasons for a focus on schools is not the risk to students, but the risk that in-person schooling poses to teachers and family members, as well as its impact on the trajectory of the overall epidemic. Yet, few studies have focused on the risk in-person school poses to household members ( 15 ).…”
Section: Main Textmentioning
confidence: 99%
“…In-person learning increases teachers’ exposure and might be expected to increase their risk of becoming infected,13 but accumulating evidence shows that teachers and school staff are not at higher risk of hospital admission or death from covid-19 compared with other workers 1415. Teacher absence because of confirmed covid-19 in England was similar in primary and secondary schools in the autumn term,16 despite secondary schoolchildren having much higher rates of SARS-CoV-2 infection 17.…”
mentioning
confidence: 99%